kil-kor regulon of promiscuous plasmid RK2: structure, products, and regulation of two operons that constitute the kilE locus. - Kornacki, J A (1993)
The kil-kor regulon of IncP plasmid RK2 is a complex regulatory network that includes genes for replication and conjugal transfer, as well as for several potentially host-lethal proteins encoded by the kilA, kilB, and kilC loci. While kilB is known to be involved in conjugal transfer, the functions of kilA and kilC are unknown. The coregulation of kilA and kilC with replication and transfer genes indicates a possible role in the maintenance or broad host range of RK2. In this work, we found that a fourth kil locus, designated kilE, is located in the kb 2.4 to 4.5 region of RK2 and is regulated as part of the kil-kor regulon. The cloned kilE locus cannot be maintained in Escherichia coli host cells, unless korA or korC is also present in trans to control its expression. The nucleotide sequence of the kilE region revealed two potential multicistronic operons. The kleA operon consists of two genes, kleA and kleB, predicted to encode polypeptide products with molecular masses of 8.7 and 7.6 kDa, respectively. The kleC operon contains four genes, kleC, kleD, kleE, and kleF, with predicted products of 9.2, 8.0, 12.2, and 11.3 kDa, respectively. To identify the polypeptide products, each gene was cloned downstream of the phage T7 phi 10 promoter and expressed in vivo in the presence of T7 RNA polymerase. A polypeptide product of the expected size was observed for all six kle genes. In addition, kleF expressed a second polypeptide of 6 kDa that most likely results from the use of a predicted internal translational start site. The kleA and kleC genes are each preceded by sequences resembling strong sigma 70 promoters. Primer extension analysis revealed that the putative kleA and kleC promoters are functional in E. coli and that transcription is initiated at the expected nucleotides. The abundance of transcripts initiated in vivo from both the kleA and kleC promoters was reduced in cells containing korA or korC. When korA and korC were present together, they appeared to act synergistically in reducing the level of transcripts from both promoters. The kleA and kleC promoter regions are highly homologous and contain two palindromic sequences (A and C) that are the predicted targets for KorA and KorC proteins. DNA binding studies showed that protein extracts from korA-containing E. coli cells specifically retarded the electrophoretic mobility of DNA fragments containing palindrome A. Extracts from korC-containing cells altered the mobility of DNA fragments containing palindrome C. These results show that KorA and KorC both act as repressors of the kleAand kleC promoters. In the absence of korA and korC, expression of the cloned kleA operon was lethal to E.coli cells, whereas the cloned kleC operon gave rise to slowly growing, unhealthy colonies. Both phenotypes depended on at least one structural gene in each operon, suggesting that the operons encode genes whose products interact with critical host functions required for normal growth and viability. Thus, the kilA, kilC, and kilE loci of RK2 constitute a cluster of at least 10 genes that are coregulated with the plasmid replication initiator and the conjugal transfer system. Their potential toxicity to the host cell indicates that RK2 is able to establish a variety of intimate plasmid-host interactions that may be important to its survival in nature.